Financial markets in Nigeria - Nnanna, O. J.; Englama, A.; Odoko, F. O.; Central Bank of Nigeria (Abuja [Nigeria] : Central Bank of Nigeria, 2004)
The book is an indepth study of financial markets, assessing the impact of the shift in policy from direct to indirect instruments of monetary management since the early 1990s. The book's scope is from 1960 - 2003 although reference is made to the pre - 1960 era when financial markets were at rudimentary stages. The study draws from the existing literature on financial markets and reports of various operators in the Nigerian financial markets. In discussing the various segments of the Nigerian financial markets, the existing literature, reports and balance sheets of financial market institutions were reviewed and analyzed.
Includes bibliographical references.
rpm 02/09/16, opc30/12/16
Loans
Keywords: Finance; Capital market; Nigeria